Desa Kungkai Baru Kecamatan Air Periukan Kabupaten Seluma 2004-2021 - Sri Fitri Wulandari; Kaksim; Meldawati (Program Studi Pendidikan Sejarah Universitas Riau, 2023)
This thesis examines Kungkai Baru Village, Air Periukan District, Seluma Regency 2004-2021. The Kungkai Baru Village community is a division of Sukarsari Village in 2004. The Kungkai Baru Village community are transmigrants originating from Yogyakarta, Ngapak, West Java, East Java where they are ethnic Balinese and Bugis, as well as ethnically indigenous people (serawai) who have lived since 1982 which at that time was called UPT Air Periukan, through the general transmigration program. The formulation of the problem in this research is as follows: What is the history of the formation of Kungkai Baru Village, Air Periukan District, Seluma Regency and how is the development of the life of the people of Kungkai Baru Village, Air Periukan District, Seluma Regency 2004-2021. This study uses historical research methods which include four stages, namely: (1) heuristics is the collection of data in the form of archives, documents, interviews, documentation. (2) source criticism, namely the stage of processing data sources of information obtained both verbally and in writing, researchers through external and internal. (3) interpretation, namely the reinterpretation of information that has been obtained and linked between one fact and another, selected and screened so that it is deemed relevant. (4) historiography, namely the stage of writing or the results of historical research carried out in the form of written works (thesis). The results showed that Kungkai Baru Village existed or was founded in 2004, precisely at the division of Sukarsari Village into 3 villages namely Sukarsari Village, Tawang Rejo Village, and Kungkai Baru Village. These three villages were transmigration areas implemented by the government through the general transmigration program in 1982-1983. The origin of the name Kungkai Baru Village is taken from the Serawai language, where Kungkai is waters and Baru in Indonesian means it has never existed. The life of the people in Kungkai Village has shown progress which we can see by the physical changes.